2019
DOI: 10.1111/joor.12843
|View full text |Cite
|
Sign up to set email alerts
|

The therapeutic role of bone marrow stem cell local injection in rat experimental periodontitis

Abstract: Mesenchymal stem cell therapy brings hope for regenerating damaged periodontal tissues. The present study aimed to investigate the therapeutic role of local bone marrow stem cell (BMSC) injection in ligation-induced periodontitis and the underlying mechanisms. Alveolar bone lesion was induced by placing ligatures subgingivally around the bilateral maxillary second molars for 28 days. The alveolar bone lesion was confirmed by micro-CT analysis and bone histomorphometry. Allogeneic BMSC transplantation was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…It has been confirmed that the majority of osteoblasts colonizing the implant surface are generated from BMSCs, contributing significantly to osseointegration (30,31). Meanwhile, several studies have reported that BMSCs can be effectively used for the treatment of periodontitis (14,32,33). However, the viability and osteogenic differentiation of BMSCs can be downregulated in an inflammatory environment, which directly results in treatment failure (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that the majority of osteoblasts colonizing the implant surface are generated from BMSCs, contributing significantly to osseointegration (30,31). Meanwhile, several studies have reported that BMSCs can be effectively used for the treatment of periodontitis (14,32,33). However, the viability and osteogenic differentiation of BMSCs can be downregulated in an inflammatory environment, which directly results in treatment failure (34).…”
Section: Discussionmentioning
confidence: 99%
“… 10 The bone marrow mesenchymal stem cell injection in a rat model exerts immunomodulatory effects at the defect sites and contributed to the periodontal repair. 11 But the drawbacks lie in the cell loss, poor engraftment, inadequate localization, spreading into surrounding tissues 12 and loss of cell fate control. 13 …”
Section: Traditional Strategiesmentioning
confidence: 99%
“…Peri-implantitis is induced with ligature of silk suture at cervical part of implant that will lead to local inflammation and alveolar bone loss to mimic the clinical peri-implantitis. This procedure is modified from procedure to induce periodontitis [16,17].…”
Section: Surgery and Ligature Designmentioning
confidence: 99%
“…Upon the reported 50.5% periimplant osseointegration in normal control implants [15], we arrived at our hypothesis that implantation at maxillary diastema in rats could provide a high level osseointegration that consequently may allow to have a ligature induced peri-implantitis. Ligature induction is a commonly used method in induction of periodontitis in murine models [16,17]. Ligature induced peri-implantitis will be more comparable than that of the pre-coating method reported by Freire and coworkers [15] due to the former is to induce inflammation after osseointegration of implant, but the latter is using a bacterial contaminated to induce inflammation at the time of implantation that will not be the case in regular clinical practice though as an experimental model, it still has its value to provide information of inflammation around an implant.…”
Section: Introductionmentioning
confidence: 99%